Gambaran Penerapan Sasaran Pasien Safety Oleh Perawat di Ruang Rawat Inap RSU Mayjen H.A Thalib Kota Sungai Penuh - Fira Dilla Zaskia; Kamariyah Kamariyah; Indah Mawarti (Jurnal Ners, 2023)
The World Health Organization states that patient safety is a serious global public health problem. Medical errors can be caused by system factors and human factors. Adverse patient safety incidents were related to surgical procedures (27%), medication errors (18.3%) and healthcare related infections (12.2%). Based on this, the application of patient safety by nurses is very important in efforts to reduce the incidence of accidents in patients. This research method uses a quantitative descriptive research design. The research was carried out in the inpatient room of the Major General H.A Thalib General Hospital, the city of Sungai Besar. The number of samples in this study were 51 people with a total sampling technique. The results showed that the application of patient safety by nurses in inpatient installations on the target of correct patient identification was 74.5%, effective communication was 68.6%, increased drug safety must be aware of 88.2%, ensure the correct location of the operation, the correct operating procedure, and the correct patient 100%, reduce the risk of infection in patients 58.8%, reduce the risk of falling in patients 62.7%.